Clusters in the Gas Dynamics and Mathematical Modeling in Mathcade the Results of the Study - Tashimbetova, Akdana; Rysbaeva, Ayman; Suleimenov, Zhazira; Kalybekova, Zhanar; Sydykova, Damelkan (International Journal of Engineering and Technology, 2018)
The concentration of clusters and the compressibility factor of nitrogen and oxygen under various conditions are calculated on the basis of the cluster model of dense gas and the Van der Waals equation. As practice shows, the cluster model gives the best agreement with experiment.Â